Opportune moments for task interruptions: examining the cognitive mechanisms underlying interruption-timing effects - Patricia Hirsch; Luca Moretti; Benedikt Leichtmann; Benedikt Leichtmann; Iring Koch; Verena Nitsch (Frontiers in Psychology, 2025)
IntroductionSeveral studies showed that task interruptions at high mental workload moments are more harmful than task interruptions at low mental workload moments. In the present study, we used a theory-driven approach to define the mental workload during primary-task execution and to examine the effects of the interruption timing on primary-task performance.MethodsParticipants performed a primary task comprising a pre-defined sequence of six subtasks, with task interruptions occasionally occurring before the second, third, or fourth subtasks. Critically, the subtasks were organized either in two lag-2 repetition triplets or in two lag-2 switch triplets (e.g., ABA-CBC vs. CBA-CAB). This set-up allowed us to test two predictions about the effects of interruption timing on the resumption costs (i.e., the performance in subtasks following an interruption compared to the performance in the same subtask in non-interrupted primary tasks). First, we expected task interruptions before the fourth subtask being the less detrimental due to the presumed chunking of the six subtasks into two triplets. Second, in lag-2 switch triplets, task interruptions before the second and third subtasks were predicted to result in comparable resumption costs. In contrast, in lag-2 repetition triplets, task interruptions before the third subtask were hypothesized to be more disruptive than those before the second subtask. This is because the mental workload should be higher due to the need to overcome subtask inhibition.ResultsWe found an interruption-timing effect with higher resumption costs for task interruptions occurring before the third subtask compared to interruptions before the second and the fourth subtasks. However, this effect did not differ across lag-2 repetition sequences and lag-2 switch sequences.DiscussionThese findings are discussed from a memory perspective and a context reconstruction perspective.